Fluid-fluid level within the ependymoma of the posterior fossa - (:unkn) unknown (My University, 2002)
We report an unusual case of an ependymoma of the posterior fossa which has an unusual location and radiological findings. MR imaging showed a mixed signal intensity containing mass centered over cerebellopontine angle cistern containing multiple cystic components with fluid-fluid levels as a result of intratumoral hemorrhage.
Keywords: Ependymoma; Fluid-fluid level; Intratumoral hemorrhage